High Uptake of FDG Along a Biliary Stent. (November 2016) - Nagasaki, Yasunari; Yamane, Hiromichi; Ochi, Nobuaki; Honda, Yoshihiro; Takigawa, Nagio
Abstract : Abstract: A 66-year-old woman presented with abdominal discomfort. Contrast-enhanced CT revealed a mass in the pancreas and multiple liver metastases. Pathological examination confirmed the mass to be primary pancreatic cancer. Endoscopic insertion of a biliary stent was performed to prevent common bile duct obstruction. Subsequently, she received combination chemotherapy, which resulted in a complete response. FDG-PET-CT after chemotherapy revealed a high uptake of FDG along the outline of the biliary stent, with complete disappearance of both the primary and metastatic tumors.